2022
DOI: 10.4103/0028-3886.359188
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Stroke Trends in A Tertiary Care Center from South India -Our Monsoon Experience

Abstract: Introduction:The unprecedented challenges during the COVID pandemic and the subsequent lockdown had resulted in a delay in treatment metrics for acute stroke. There is a rising concern that COVID-19 co-infection can adversely affect stroke outcome. We aim to investigate the impact of COVID-19 in the management of stroke patients. We also compared the differences in stroke manifestations, etiological pattern, treatment course, and outcome of acute stroke patients in COVID-19 confirmed cases.Methodology:A single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
0
2
Order By: Relevance
“…The results for the probable need for assistance due to major neurological deficits, as indicated by mRS > 2 points, show significantly lower rates at the beginning of COVID-19 wave 2 in August 2020 and at the beginning of COVID-19 wave 3 in March 2021. Some studies found no differences in NIHSS and mRS at admission [ 5 , 7 ], while others found differences [ 6 , 24 , 25 ], but in contrast to our results, patients had higher presenting NIHSS and mRS during the pandemic. However, the periods considered in these studies were short and involved small numbers of cases.…”
Section: Discussioncontrasting
confidence: 99%
“…The results for the probable need for assistance due to major neurological deficits, as indicated by mRS > 2 points, show significantly lower rates at the beginning of COVID-19 wave 2 in August 2020 and at the beginning of COVID-19 wave 3 in March 2021. Some studies found no differences in NIHSS and mRS at admission [ 5 , 7 ], while others found differences [ 6 , 24 , 25 ], but in contrast to our results, patients had higher presenting NIHSS and mRS during the pandemic. However, the periods considered in these studies were short and involved small numbers of cases.…”
Section: Discussioncontrasting
confidence: 99%
“…Hospital based studies have shown that during lockdown due to pandemic restrictions, there was an increase in delays in stroke and cardiac patients reaching the hospitals. 35 , 36 Our sub-analysis, though small in numbers, did not reveal higher health system access delay in deaths that occurred during the period when lockdown was imposed. The delays assessed qualitatively and quantitatively did not always arrive at same conclusion, for example, there might be no delays reported qualitatively yet they may reach AHF after 1 h. Though a formal sample size estimation was not done as a geographical defined area was saturated, the sample size appears to be sufficient to estimate proportion of delays, though not separately for stroke.…”
Section: Discussioncontrasting
confidence: 57%